The effect of brazing temperature on the titanium/glass-ceramic bonding - Guedes, A. (1999)
The aim of this work is to study the effect of time and brazing temperature on the interfacial microstructure and mechanical properties of the joint obtained by active metal brazing between c.p. titanium and a fluorosilicate machinable ceramic±glass using a 64Ag-34.5Cu-1.5Ti (wt%) brazing alloy. The reaction between the brazing alloy and the two materials leads to the formation of several interfacial reaction layers with different compositions, morphologies and extensions. These layers are constituted by various reaction products that ensure chemical bonding between the two materials, their stability and capability to accommodate the discontinuity of properties across the interface determining the success of the joining. The interfacial microstructure was analysed by SEM and the composition of each reaction layer was investigated by EDS. Microhardness tests were performed across the interfacial zone and the global interfacial mechanical behaviour was evaluated by means of shear tests.